A Six Year Follow-up Study on the Influence of Silent Ischemic Brain Lesions on Cognitive Function and Brain Atrophy in Elderly People - Okada, Kazunori; Yamaguchi, Shuhei; Kobayashi, Shotai; Oguro, Hiroaki (Nihon Rōnen Igakkai zasshi, 2000)
Methods; To investigate the influence of silent ischemic brain lesions (silent brain infarction (SBI) and periventricular hyperintensity (PVH)) on cognitive function and brain atrophy, we studied MRI and cognitive tests in 27 healthy elderly people (above 65 years old) for 6 years. We examined Okabe's Scale for verbal intelligence, Koh's Block Design Test for performance intelligence and Zung's Self-rating Depression Scale (SDS). On MRI, lesions with high intensity on T2-weighted image and low intensity on T1-weighted image, and which were larger than 3mm were diagnosed as SBI. The PVH was classified into 5 grades (0-4), and we divided the subjects into the PVH 0-1 group and the PVH 2-4 group. We evaluated brain atrophy using the ventricular area index (VAI) (the ratio of ventricular area to intracranial area at the level of lateral ventricle) on MRI by NIH image 1.55 (Macintosh). Results; The SBI group and the PVH 2-4 group showed significant decline in Okabe's Score, and Koh's IQ, increase in SDS and VAI during six years. On the other hand, the non-SBI and the PVH0-1 group showed a decline only in Okabe's score, and an increase in VAI. The rate of change in VAI was significantly higher in the subjects with SBI than those without it. However, there was no significant difference in the VAI change rate between the PVH 2-4 group and the PVH 0-1 group. Conclusion; Silent ischemic brain lesions such as SBI and PVH may have significant influence on decline of cognitive functions and progression of brain atrophy even in healthy elderly people.